TEN YEARS AFTER ROMANIA'S ACCESSION TO THE EUROPEAN UNION: COSTS, BENEFITS AND PERSPECTIVES - Dan VĂTĂMAN (Challenges of the Knowledge Society)
This year we celebrate ten years since Romania became full-fledged Member of the European Union, a decade in which our country have seen a remarkable evolution marked by huge transformations and irreversible processes of reform which led to the modernization of the society and economic development. Despite these undeniable achievements which had a positive impact on the quality of life of Romanian citizens, a great number of people are disappointed because still facing poverty and economic underdevelopment, aspect that makes them to express disapproval of the fact that Romania is a Member State of European Union. In the light of this paradox, the aim of this study is to put in antithesis the advantages and disadvantages of the Romania's accession to the European Union, all this in relation to the current international context and the challenges facing the European Union.